A plant virus protein, NIa-pro, interacts with Indole-3-acetic acid-amido synthetase, whose levels positively correlate with disease severity - Gnanasekaran, Prabu; Zhai, Ying; Kamal, Hira; Smertenko, Andrei; Pappu, Hanu R. (Frontiers in Plant Science, 2023)
Potato virus Y (PVY) is an economically important plant pathogen that reduces the productivity of several host plants. To develop PVY-resistant cultivars, it is essential to identify the plant-PVY interactome and decipher the biological significance of those molecular interactions. We performed a yeast two-hybrid (Y2H) screen of Nicotiana benthamiana cDNA library using PVY-encoded NIa-pro as the bait. The N. benthamiana Indole-3-acetic acid-amido synthetase (IAAS) was identified as an interactor of NIa-pro protein. The interaction was confirmed via targeted Y2H and bimolecular fluorescence complementation (BiFC) assays. NIa-pro interacts with IAAS protein and consequently increasing the stability of IAAS protein. Also, the subcellular localization of both NIa-pro and IAAS protein in the nucleus and cytosol was demonstrated. By converting free IAA (active form) to conjugated IAA (inactive form), IAAS plays a crucial regulatory role in auxin signaling. Transient silencing of IAAS in N. benthamiana plants reduced the PVY-mediated symptom induction and virus accumulation. Conversely, overexpression of IAAS enhanced symptom induction and virus accumulation in infected plants. In addition, the expression of auxin-responsive genes was found to be downregulated during PVY infection. Our findings demonstrate that PVY NIa-pro protein potentially promotes disease development via modulating auxin homeostasis.